KONDISI SANITASI PASAR SOPONYONO KECAMATAN RUNGKUT KOTA SURABAYA TAHUN 2022 - Zulfa Sekar Maharani; Suprijandani Suprijandani; Darjati Darjati; Fitri Rokhmalia; Ferry Kriswandana (Jurnal Hygiene Sanitasi, 2022)
Soponyono market is al traditional malrkelt that plays an important role in providing safe food. Also, the market can become a place of disease transmission, so it is very important to monitor and control the cleanliness or health of the market environment. Thel purpose of this research was describe the hygiene status of the Soponyono market which includes market formation, market cleanliness and market PHBS, then analyzed using SWOT analysis (strelngths, welalknelssels, opportunitiels alnd threlalts). The results of the SWOT analysis will form the market hygiene position development strategy. This research was descriptive type of research that uses observation sheets to obtain results for the sanitary conditions of the Soponyono Market. Based on the study results, thel sanitary condition in Soponyono Market, category Rungkut District, Surabaya City was generally good and in the eligiblel as per the existing regulations such as market buildings (80.6%), market cleanlinelss in the eligible category (68.1%), and clean alnd healthy behavior (59%) category requirements. The results of the SWOT anallysis on the sanitary state of the Soponyono market are in Quadrant I (Aggressive). It is recommended that market managers monitor the sanitary condition of the market in accordance with Decree 519/MENKES/SK/VI/2008 of the Minister of Health of the Republic of Indonesial relating to the implementation of healthy markets. The strategy used is to take advantage of all the strengths of the clean market conditions and to talkel advantage of opportunities as much as possible.